INDONESIA DALAM LIBERALISASI PERDAGANGAN (PERSPEKTIF POLITIK DAN BUDAYA HUKUM) - Fahrazi, Mahfud (Jurnal Yuridis, 2015)
In this discussion, the author tries to illustrate the complexity of the problems or weakrtesses Indonesian involvement in trade liberalization, both in terms of aspects of political, legal and cultural aspects related to the position of Indonesia as a developing country. Based on all the above explanation, then that should be a basic question in this paper, namely: What factors the complexity of the weakrtess of Indonesia in trade liberalization. There are some problems or weakrtesses is the basis why it failed to achieve the interests and economic benefits expected Indonesian government, namely (1) The weakrtess of economic diplomacy. Negotiators consisting of diplomats and officials of the technical departments have weaknesses. Diplomats may dominate in terms of language but not in terms of substance, while officials from the technical department to master the substance but did not master the language. This weakness is compounded because of the very few institutions both have members who master the skills to design a legal sentence. (2) Lack of awareness and attitude of the national industry to utilize the legal instruments of trade remedies. (3) The weakness of the latter which will be discussed in this paper is related to the bargaining position of developing countries when dealing with the industrialized countries.